Pengaruh Penambahan Biotin Pada Media Pertumbuhan Terhadap Produksi Sel Aspergillus niger - Wuryanti, Wuryanti (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2008)
Aspergillus niger is one of microorganisms which has potensial as L-asparaginase source. Biotin are vitamins soluble in water and have function to facilitate the increasing cell growth. The research has purposes to determine the influences of adding biotin into growing medium of Aspergillus niger to its cell production. The results from research show that the optimum incubation time for producing biomass weight of Aspergillus niger was at the 48th hour. Addition of biotin 0.1 mg/L into growing medium of Aspergillus niger might increase biomass weight of Aspergillus niger until 40.17 %.